Common beans in Latin America and their constraints - Schoonhoven, Aart van; Voysest Voysest, Oswaldo (International Center for Tropical Agriculture, 1989)
Information is given on the situation of beans in Latin America, in terms of producing regions, national consumption and exports in various countries, classes of beans grown, production structure, and constraints to production. Main limitations to bean production are diseases and insect pests, which significantly lower on-farm yield. Web blight, BGMV, and anthracnose are some of the main diseases affecting beans. The most important insect pests in Latin America include leafhoppers (Empoasca spp.), cutworms, the pod weevil (Apion godmani), the Mexican bean beetle (Epilachna varivestis), slugs (Vaginulus plebeius and Limax maximus), and storage insects (Acanthoscelides obtectus and Zabrotes subfasciatus). Soil related constraints, drought, the use of unsuitable cv., and socioeconomic factors are also classified as limiting bean production. Major disease problems per country and a climate classification of bean-producing regions are given in table form. (CIAT)